2015
DOI: 10.1353/hpu.2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Survival between Housed and Homeless individuals with HIV, San Francisco, 2002–2011

Abstract: San Francisco (SF), a city with large HIV-infected and homeless populations, expanded supportive housing for HIV-infected people in 2007. We used the SF HIV/AIDS registry to compare survival between people who were homeless and who were housed at time of HIV diagnosis from 2002 through 2011. Housing status was obtained from medical records and deaths from local, state, and national vital registration. Survival was estimated using the Kaplan-Meier product-limit method. Ten percent of the 5,474 cases were homele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Among all PLWH in San Francisco diagnosed with HIV from 2002 to 2006, the five-year survival rate for homeless individuals was 79% compared to 92% among housed individuals (p<0.001) 6 . However, among persons diagnosed with HIV more recently from 2007 to 2011 there was no difference in the five-year survival rate between homeless and housed people (p=0.40) 6 . A study analyzing a permanent supportive housing program in San Francisco found that among 6,558 AIDS cases diagnosed from 1996-2006 in San Francisco, the fiveyear survival rate for persons who were homeless was 67% compared to 81% among those who were housed under permanent supportive housing (p<0.0001) 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Among all PLWH in San Francisco diagnosed with HIV from 2002 to 2006, the five-year survival rate for homeless individuals was 79% compared to 92% among housed individuals (p<0.001) 6 . However, among persons diagnosed with HIV more recently from 2007 to 2011 there was no difference in the five-year survival rate between homeless and housed people (p=0.40) 6 . A study analyzing a permanent supportive housing program in San Francisco found that among 6,558 AIDS cases diagnosed from 1996-2006 in San Francisco, the fiveyear survival rate for persons who were homeless was 67% compared to 81% among those who were housed under permanent supportive housing (p<0.0001) 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Among all PLWH in San Francisco diagnosed with HIV from 2002 to 2006, the five-year survival rate for homeless individuals was 79% compared to 92% among housed individuals (p < 0.001) 6 . However, among persons diagnosed with HIV more recently from 2007 to 2011 there was no difference in the five-year survival rate between homeless and housed people (p = 0.40) 6 . In contrast to the improvement in mortality data, a 2017 study in San odds for achieving viral suppression with individuals living in shelters (adjusted odds ratio [OR] = 0.26, 95% CI 0.12, 0.59) and those living outdoors (adjusted OR = 0.15, 95% CI 0.08, 0.29) 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Among all PLWH in San Francisco diagnosed with HIV from 2002 to 2006, the five-year survival rate for homeless individuals was 79% compared to 92% among housed individuals (p<0.001) 6 . However, among persons diagnosed with HIV more recently from 2007 to 2011 there was no difference in the five-year survival rate between homeless and housed people (p=0.40) 6 . In contrast to the improvement in mortality data, a 2017 study in San Francisco reported poorer HIV viral suppression among homeless PLWH.…”
mentioning
confidence: 94%